2011
DOI: 10.4236/ijoc.2011.14032
|View full text |Cite
|
Sign up to set email alerts
|

Heterosynthesis Using Nitriles: Novel Pyrrolo[2,3-<i>b</i>]pyridines

Abstract: 2-Amino-4-benzoyl-1-arylpyrrole-3-carbonitriles react with arylidene malonodinitriles, β-ketoesters and βdiketones to afford pyrrolo[2,3-b]pyridine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A study by Lv et al, [20] described that thiazolylpyrazole analogs shown moderate to the high inhibitory action of epidermal growth factor receptor tyrosine kinase (EGFR TK) with potential antitumor activity. Molecular docking of thiazolyl-pyrazolines indicated that it has a higher binding affinity to epidermal growth factor receptor kinase [21][22][23]. Many researchers investigated the biological activities of practically substituted heterocyclic compounds [24][25][26] which are commonly used in biodegradable agrochemicals [27][28][29] from shoddy research facilities as starting materials [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lv et al, [20] described that thiazolylpyrazole analogs shown moderate to the high inhibitory action of epidermal growth factor receptor tyrosine kinase (EGFR TK) with potential antitumor activity. Molecular docking of thiazolyl-pyrazolines indicated that it has a higher binding affinity to epidermal growth factor receptor kinase [21][22][23]. Many researchers investigated the biological activities of practically substituted heterocyclic compounds [24][25][26] which are commonly used in biodegradable agrochemicals [27][28][29] from shoddy research facilities as starting materials [30][31][32].…”
Section: Introductionmentioning
confidence: 99%